PENGGUNAAN BEBERAPA SUBSTRAT PADA HIDROPONIK SAWI PAGODA SISTEM RAKIT APUNG - Hape, Teressa Septian; Astutik, Astutik; Hapsari, Ricky Indri; Sumiati, Astri (Universitas Tribhuwana Tunggadewi, 2024)
The research aims to obtain the type of substrate and dosage of AB Mix that can elevate the growth of pagoda mustard plants. The study used a completely randomized design with four substrates: wood powder, charcoal husk, sphagnum moss, and cocopeat. AB Mix uses two doses such as 6 and 8 ml/l repeated 4 times in each experiment with three plant samples. Observations included parameters of plant height, number of leaves, leaf area, wet weight of plants and roots, and dry weight of plants and roots. The results showed that the husk charcoal substrate with AB Mix 8 ml/l nutrition produces the highest wet weight of pagoda mustard plants.